2007
DOI: 10.1016/j.jembe.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food diversity on diatom selection by harpacticoid copepods

Abstract: The diversity of species assemblages which occupy a basal position in the trophic pyramid (typically unicellular algae in aquatic environments) is known to influence the interaction with organisms of higher trophic levels. A laboratory feeding experiment was conducted with cultures of three benthic diatom species (Navicula phyllepta, Grammatophora marina and Cylindrotheca closterium) as primary producers and three harpacticoid copepod species (Harpacticus obscurus, Paramphiascella fulvofasciata and Tigriopus b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 54 publications
0
25
0
1
Order By: Relevance
“…dentatum migrated into the macrophytodetritus accumulation to avoid low oxygen levels in the sediment underneath or to search for more accessible food. Harpacticoids are known to feed on a wide variety of food sources (Hicks and Coull, 1983;Lee et al, 1977), displaying species-specific food preferences (Buffan-Dubau and Carman, 2000;De Troch et al, 2012;Decho and Castenholz, 1986;Pace and Carman, 1996;Wyckmans et al, 2007). Hicks and Coull (1983) stated that the existence of a wide variety of morphologically similar species in one habitat is allowed as a consequence of harpacticoids' selective feeding.…”
Section: Harpacticoid Copepod Species Assemblage In Detritusmentioning
confidence: 99%
“…dentatum migrated into the macrophytodetritus accumulation to avoid low oxygen levels in the sediment underneath or to search for more accessible food. Harpacticoids are known to feed on a wide variety of food sources (Hicks and Coull, 1983;Lee et al, 1977), displaying species-specific food preferences (Buffan-Dubau and Carman, 2000;De Troch et al, 2012;Decho and Castenholz, 1986;Pace and Carman, 1996;Wyckmans et al, 2007). Hicks and Coull (1983) stated that the existence of a wide variety of morphologically similar species in one habitat is allowed as a consequence of harpacticoids' selective feeding.…”
Section: Harpacticoid Copepod Species Assemblage In Detritusmentioning
confidence: 99%
“…For example, Komuro et al (2005) and Buck et al (2008) reported M. trioculatus and M. chilensis at densities of up to 10 7 cells l À1 , likely making them major contributors to the local seasonal diatom maxima. Interestingly, several recent publications clearly indicate that zooplankton are able to select food items and can enhance their reproductive success by choosing, avoiding or selecting certain species (Irigoien et al, 2002;Wyckmans et al, 2007). Pico-and nanoplanktonic diatoms are found in zooplankton fecal pellets (Urban et al, 1993;Kang et al, 2003).…”
Section: Ecologymentioning
confidence: 99%
“…Copepods are selective in their feeding process (Meyer-Harms and von Bodungen 1997). The selectivity is sensitive and copepods can distinguish between food particles of different nutritional status (Cotonnec et al 2001), algal composition (Atkinson 1994;Wyckmans et al 2007), concentration (Katechakis andStibor 2004), taste (DeMott andTessier 2002) and toxicity of algae (DeMott and Tessier 2002). The relationship between primary production, grazing and the export of organic material is strongly determined by the size structure of the trophic pathways (Morales et al 1990;Froneman et al 2000).…”
Section: Introductionmentioning
confidence: 99%